2004
DOI: 10.1007/s00066-004-1234-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Brain Metastases after Whole Brain Radiotherapy

Abstract: Based on this analysis, prognostic factors for survival after WBRT in patients with brain metastases could be identified. A total of 19% (n = 44/232) survived > or = 1 year, whereas overall survival was poor. The potential value of the RPA classes in estimating the patient's prognosis could be confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
3
12
0
Order By: Relevance
“…Especially in the case of patients with breast cancer, commonly associated with a favorable outcome, it should be evaluated whether WBRT with all known side effects should be the treatment of choice as compared to SRS in patients with one to three brain metastases. In accordance with data found in the literature [12], we could show that in patients with one to three cerebral lesions, the number of brain metastases does not significantly influence overall survival. However, a number of studies found in the literature support the idea, that patients with a single brain metastasis survive longer than patients with multiple lesions [28,34,50].…”
Section: Discussionsupporting
confidence: 81%
“…Especially in the case of patients with breast cancer, commonly associated with a favorable outcome, it should be evaluated whether WBRT with all known side effects should be the treatment of choice as compared to SRS in patients with one to three brain metastases. In accordance with data found in the literature [12], we could show that in patients with one to three cerebral lesions, the number of brain metastases does not significantly influence overall survival. However, a number of studies found in the literature support the idea, that patients with a single brain metastasis survive longer than patients with multiple lesions [28,34,50].…”
Section: Discussionsupporting
confidence: 81%
“…While surgery [31] and radiosurgery [10,13] are efficient only in selected subgroups, most patients can only be treated by palliative whole-brain irradition (WBRT) with overall response rates of about 50-60% and median survival times of 3-4 months [3,5,6]. Due to the limited tolerance of the normal brain tissue to radiation and a shallow radiation dose-response curve [24], increased doses of radiation have failed to improve outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple prognostic factors have been shown to be related to patient survival in the context of brain metastases which include: performance status, extracranial disease, age, controlled primary, primary site, interval between primary disease and brain metastases, number/volume of brain metastases, and clinical response to steroids [1][2][3][4][5][6][7][8][9][10][11]. The Radiation Therapy Oncology Group (RTOG) Recursive Partitioning Analysis (RPA) brain metastases prognostic index is the oldest system currently in use [2,[12][13][14][15][16]. However, the utility of the system has been limited by the large relative proportion of patients within the intermediate-risk group, as has been previously highlighted by several investigators [17][18].…”
mentioning
confidence: 99%